Liquid braze surface tension determination algorithms implemented in brazeability analysing system - Sankowski, Dominik; Bąkała, Marcin; Wojciechowski, Rafał; Albrecht, Andrzej (Wydawnictwa AGH, 2010)
In this article, the methods of surface tension determination implemented in Brazeability Analysing System are shown. The authors have presented methodology and analytical concept of surface tension measurement using two methods: plate- and maximum pressure in gas bubble method. The construction of automated system for carrying out measurement experiments and calculating quantity result of surface tension is shortly discussed. The results of example experiments for Sn60Pb40 and SnAg3,5 brazes are presented.

W artykule omówiono metody wyznaczania napięcia powierzchniowego zaimplementowane w urządzeniu tester lutowności. Autorzy zaprezentowali metodologię oraz podstawy analityczne pomiaru napięcia powierzchniowego z wykorzystaniem metod: płytkowej oraz maksymalnego ciśnienia w pęcherzyku. W artykule przedstawiono również budowę automatycznego systemu do przeprowadzania eksperymentów pomiarowych i wyznaczania wartości napięcia powierzchniowego. Zamieszczono również przykładowe dane pomiarowe dla lutów Sn60Pb40 oraz SnAg3,5.
Algorytmy wyznaczania napięcia powierzchniowego ciekłych lutów zaimplementowane w testerze lutowności
Automatyka
Keywords: industrial system; measurements automation; material engineering; informatyka przemysłowa; automatyzacja pomiarów; brazing; inżynieria materiałowa; lutowanie; surface tension; napięcie powierzchniowe